2015
DOI: 10.1590/s0036-46652015000500002
|View full text |Cite
|
Sign up to set email alerts
|

NEW PRIMERS FOR DETECTION OF Leishmania infantum USING POLYMERASE CHAIN REACTION

Abstract: SUMMARY Leishmania infantum causes visceral leishmaniasis (VL) in the New World. The diagnosis of VL is confirmed by parasitological and serological tests, which are not always sensitive or specific. Our aim was to design new primers to perform a Polymerase Chain Reaction (PCR) for detecting L. infantum. Sequences of the minicircle kinetoplast DNA (kDNA) were obtained from GenBank, and the FLC2/RLC2 primers were designed. Samples of DNA from L. infantum, Leishmania amazonensis,Leishmania braziliensis, Leishman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…Santamaria et al (2005) determined the LoD in 1 equivalent parasite in the PCR using kDNA (Santamaria et al, 2005), unlike the findings of this study, the LoD of this technique with the same marker was 1 × 10 -1 parasites equivalents/mL ( Figure 1 ). These results are consistent with those described by other authors where is reported that kDNA presents high copy number and can detect up to less than one parasite in conventional PCR (de Bruijn and Barker, 1992; Mary et al, 2004; Francino et al, 2006; Oliveira et al, 2011; Gualda et al, 2015). The LoD for the assays directed to the 18S and ITS-1 markers was 1 × 10 0 parasites equivalents/mL, similar results reported by Deborggraeve et al (2008) where the technique was able to detect up to 1 parasite/180 μL.…”
Section: Discussionsupporting
confidence: 93%
“…Santamaria et al (2005) determined the LoD in 1 equivalent parasite in the PCR using kDNA (Santamaria et al, 2005), unlike the findings of this study, the LoD of this technique with the same marker was 1 × 10 -1 parasites equivalents/mL ( Figure 1 ). These results are consistent with those described by other authors where is reported that kDNA presents high copy number and can detect up to less than one parasite in conventional PCR (de Bruijn and Barker, 1992; Mary et al, 2004; Francino et al, 2006; Oliveira et al, 2011; Gualda et al, 2015). The LoD for the assays directed to the 18S and ITS-1 markers was 1 × 10 0 parasites equivalents/mL, similar results reported by Deborggraeve et al (2008) where the technique was able to detect up to 1 parasite/180 μL.…”
Section: Discussionsupporting
confidence: 93%
“…For DNA extraction, the NucleoSpin® Tissue Kit (Macherey-Nagel, GmbH & Co. KG, Germany) was used according to the manufacturer's instruction. Then, the extracted DNA was amplified using a SYBR® Green Real-Time PCR targeting a kDNA gene (230 bp) with the forward primer FLC2 (5′-GTCAGTGTCGGAAACTAATCCGC-3′) and the reverse primer RLC2 (5′-GGGAAATTGGCCTCCCTGAG-3′) designed by Gualda et al [ 22 ]. The cycling conditions, performed in a 7900HT thermocycler (Applied Biosystems, California, USA), were as follows: the final reaction volume was 20 μ l with 10 μ l QuantiFast™ SYBR® Green PCR Master Mix 2x concentrated (Qiagen, Germany), 6.6 μ l RNase-free water, 0.2 μ l (0.1 μ mol) of each specific primer, and 3 μ l of the DNA isolated from the blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…Positive samples by qPCR were further tested by a species-specific conventional PCR assay, using the primers FLC2 (5'-GTCAGTGTCGGAAACTAATCC GC-3') and RLC2 (5'-GGGAAATTGGCCTCCCTGAG-3'), which amplify a 230 bp fragment of L. infantum kDNA 13 . The final reaction volume was 25 μL, consisting of 1 X buffer, 0.2 mM dNTP (dATP, dCTP, dGTP, and dTTP), 1.5 mM MgCl 2 , 1.5 U Taq Polymerase (Invitrogen,Thermo Scientific, Waltham, MA, USA), 0.4 pmol of each primer and 2 μL of genomic DNA.…”
Section: Molecular Diagnosismentioning
confidence: 99%